Taman Burung Dengan Pendekatan Arsitektur Postmodern Metafora - Muhammad Hafiz I. S.; Ratna Amanati; Mira Dharma S (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Bird is one of animals that comes in various species and spreads in almost every part of Earth’s surface. However, certain specieses of birds is on the verge of extinction. Nature destruction andpoaching are the causes of the extinction. In Indonesia, there are 131 kinds of birds whose existence is endangered. Therefore, a medium to acomodate endangered birds is needed and it’s called as Bird Park. The Bird Park is designed using Metaphoric Postmodern Architecture approach. The purpose of using Metaphoric Postmodern Architecture is to create a replica of bird’s real habitat. Postmodern Metaphoric Architecture is a design theory that takes the shape and characteristics of an object andapplied it to the building’s appearance. Through this Postmodern Metaphoric theme, we are able to get the concept of ‘Unity in Diversity’. This is to combine and connect the functions of the Bird Park as means of recreation, education, and conservation. Through this Postmodern Metaphoric Architecture theme and the concept of ‘Unity in Diversity’, we are able to get the shapes andcharacteristics of birds that can be applied on the mass arrangement and façade pattern of the Bird Park.Keywords: Extinction, Bird Park, Methaporic Postmodern Architecture